2002
DOI: 10.1542/peds.109.2.e26
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Manifestations of Fulminant Enterovirus 71 Infection

Abstract: ABSTRACT. Background. The pathogenesis of acute pulmonary edema and cardiac collapse after enterovirus 71 (EV71) infection are not completely understood.Objective. To determine the hemodynamic features and the mechanism of pulmonary edema (PE) after EV71 infection by direct intracardiac monitoring.Design. Prospective clinical and laboratory study at a tertiary medical center.Participants. Five consecutive infants, ages 2 to 13 months, with EV71 infection-proved by viral isolation in 4 and antibody in 1-with PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 18 publications
10
47
0
Order By: Relevance
“…In this circumstance, PE is thought to occur secondarily to direct hydrostatic force as well as to increased permeability from endothelial injury [27]. Hemodynamic studies of patients with PE revealed normal cardiac function and normal pulmonary hydrostatic pressure [28]. Pathologic studies showed no myocardium necrosis and calcification [4,26].…”
Section: Pathogenesis Of Brainstem Encephalitismentioning
confidence: 99%
“…In this circumstance, PE is thought to occur secondarily to direct hydrostatic force as well as to increased permeability from endothelial injury [27]. Hemodynamic studies of patients with PE revealed normal cardiac function and normal pulmonary hydrostatic pressure [28]. Pathologic studies showed no myocardium necrosis and calcification [4,26].…”
Section: Pathogenesis Of Brainstem Encephalitismentioning
confidence: 99%
“…8 suggested that the pathogenesis of heart failure and subsequent PE/PH is related to systemic inflammatory response syndrome rather than myocarditis. 9 The inotrope demand can be extraordinarily high during the hypotension period. Eight patients (five survived) had an IE higher than 45, an indication in some medical centers for use of extracorporeal membrane oxygenation (ECMO).…”
Section: Predictors Associated With Acute Fatality and Ventilatormentioning
confidence: 99%
“…98 Severe systemic and pulmonary hypertension is not always seen in children with EV71-associated pulmonary oedema. [99][100][101] This disparity might arise because the changes in vascular pressures in neurogenic pulmonary oedema are only transient. 96 Some commentators have argued that cardiac dysfunction is a major contributor to the pulmonary oedema.…”
mentioning
confidence: 99%